Molecular Organization and Chromosomal Localization Analysis of 5S rDNA Clusters in Autotetraploids Derived From Carassius auratus Red Var. (♀) × Megalobrama amblycephala (♂) - Qin, QinBo; Liu, QiWen; Wang, ChongQing; Cao, Liu; Zhou, YuWei; Qin, Huan; Zhao, Chun; Liu, ShaoJun (Frontiers in Genetics, 2019)
The autotetraploid fish (4n = 200, RRRR) (abbreviated as 4nRR) resulted from the whole genome duplication of red crucian carp (Carassius auratus red var., 2n = 100, RR) (abbreviated as RCC). During investigation of the influence of polyploidization on organization and evolution of the multigene family of 5S rDNA, molecular organization and chromosomal localization of the 5S rDNA were characterized in autotetraploid fish. By sequence analysis of the coding region (5S) and adjacent non-transcribed spacer (NTS), three distinct 5S rDNA units (type I: 203 bp; type II: 340 bp; and type III: 477bp) were identified and characterized in 4nRR. These 5S rDNA units were inherited from their female parent (RCC), in which obvious base variations in NTS and array recombination of repeat units were found. Using fluorescence in situ hybridization employing different 5S rDNA units as probes, these 5S rDNA clusters were localized in chromosomes of 4nRR, respectively, and showed obvious loss of chromosomal loci (type I and type II). Our data revealed genetic variation of the 5S rDNA multigene family in the genome of autopolyploid fish. Furthermore, results provided new insights into the evolutionary patterns of this vertebrate multigene family.